Analisis Katak sebagai Obat Kesehatan: Studi Takhrij dan Syarah Hadis Pendekatan Medis - Salma Salfani; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about frogs as medicine. This study uses a qualitative approach through the takhrij and syarah hadith methods by applying contemporary analysis in the medical and clinical fields. The results and discussion show that the hadith of the frog as a quality medicine hasan li ghairihi according to the takhrij review so that it can be used as evidence in everyday life. While the syarah of this hadith shows that frogs have very high nutrition and can be used as the main animal protein. In addition, frogs are also believed to be able to cure some mild or severe diseases such as cancer. According to research, although frogs have high nutritional value, their digestive system contains nematode worms that can harm the human metabolic system. In addition, the majority of scholars also stated that the Messenger of Allah. prohibits killing the frog because it is forbidden to be consumed let alone used as medicine.